Advances in Observing and Understanding Small-Scale Open Ocean Circulation During the Gulf of Mexico Research Initiative Era - D'Asaro, Eric A.; Carlson, Daniel F.; Chamecki, Marcelo; Harcourt, Ramsey R.; Haus, Brian K.; Fox-Kemper, Baylor; Molemaker, M. Jeroen; Poje, Andrew C.; Yang, Di (Frontiers in Marine Science, 2020)
Prediction of the distribution of buoyant oil, plastics, flotsam and marine organisms near the ocean surface is a long-standing fundamental problem of practical importance. Here, progress in this area during the time of the Gulf of Mexico Research Initiative (GoMRI) (2012-2019) is synthesized, emphasizing the well-known accumulation of floating material into highly concentrated streaks on horizontal scales of meters to 10’s of kilometers. In the pre-GoMRI period, two new paradigms were developed: the importance of submesoscale frontal dynamics on the larger scales and of surface-wave-driven Langmuir turbulence on the smaller scales, with a broad transition occurring near 100 m. Rapid progress resulted from the combination of high resolution numerical modeling tools, mostly developed before GoMRI, and new observational techniques developed during GoMRI. New designs for inexpensive and biodegradable satellite tracked surface drifters and new techniques for aerial tracking of surface drift cards enabled the deployment of thousands of such drifters to measure surface currents and to act as calibrated surrogates for oil. Progress in using radar and optical remote sensing of surface waves enabled mapping of surface currents from ships and aircraft. These new tools, combined with traditional oceanographic tools, enabled a set of coordinated measurement programs which supported and expanded the new paradigms. Floating material was found to both accumulate at submesoscale fronts and to disperse by following these fronts as they moved, leading to both higher concentrations and increased dispersion. Analyses confirmed the distinct submesoscale dynamics of this process and complexity of the resulting fields. Existing tools could be developed into predictive models of submesoscale statistics; prediction of individual submesoscale features is limited by data. Away from fronts, measured rates of accumulation of material in and beneath surface windrows was found to be consistent with Langmuir turbulence, but highly dependent on the rise rate of the material and thus, for oil, on the droplet size. Models of this process were developed and tested and could be further developed into predictive tools. Both the submesoscale and Langmuir processes are sensitive to coupling with surface waves and air-sea flux processes; this is a promising area for future studies.